Phenol removal by newly isolated Acinetobacter baumannii strain Serdang 1 in a packed-bed column reactor - Yadzir, Z.H.M. (Taylor and Francis Inc., 2016)
A newly isolated Acinetobacter baumannii strain Serdang 1 was explored for its potential in phenol remediation in batch and continuous system. An immobilization cell system has been successfully developed to remove phenol in a batch system as high as 2,000Â mg/L in 12Â d at a rate of 6.04Â mg/L/h. Repeated use of immobilized cells as many as five cycles was shown without any loss of activity. The continuous system in a packed-bed reactor achieved 65â77 phenol removal at the rate of 38.4Â mg/L/h for 200Â mg/L influent, which was almost three fold higher than the batch system. Low influent flow rate at 1.5Â mL/min and bed height-to-diameter ratio of 15.2 reached steady state faster than the higher flow rate, and the percentage of phenol removal was also higher. Â© 2015 Balaban Desalination Publications. All rights reserved.